ANALISIS EFISIENSI PEMASARAN KUNYIT DI DESA MENUNGGAL KECAMATAN KEDAMEAN KABUPATEN GRESIK - administrator, administrator; Subkhi, Ahmad; Humaidi, Faisol; Susanto, Heri (Jurnal Agribisnis Wijaya Putra Surabaya, 2022)
This research has purpose for (1) Find out how much employment opportunities are created from tomato farming in the Pengalangan Village. (2) Knowing the factors of land area, number of commodities and cropping patterns influence the employment opportunities of tomato farmers in Pengalangan Village. (3) Knowing the influence of socioeconomic factors (education level, farming experience, cosmopolitan level, number of family dependents, and land area) on the productivity of tomato farmer land in Pengalangan Village. This research was conducted in Pengalangan Village, Menganti subdistrict, Gresik Regency. Determination of the research area was done purposively. The sample in this research are farmers who cultivate tomatoes. Sampling is done in Simple Random Sampling. The data used are primary data and secondary data. The results of this study were the first large employment opportunities created by vegetable tomato farming for each sample farmer, ranging from sample farmers with the smallest employment opportunities of 15.4 HKP / year to farmers with employment opportunities of 315.3 HKP / year. The effect of factors on land area, cropping patterns and the number of commodities simultaneously has a significant effect on the employment opportunities of vegetable tomato farmers. The influence of socio-economic factors (education level, farming experience, cosmopolitan level, number of family dependents and land area) have a significant effect on the productivity of the land of tomato farmersKeyword: social, economic, employment, productivity